(untitled) (Ustozlar uchun, 2026)
In recent years, laparoscopic cholecystectomy (LC) has become the gold standard for the surgical treatment of gallbladder diseases. However, literature analysis indicates that the risk of complications, particularly bile leakage, remains significant. This study analyzed scientific literature, including original articles, systemic reviews, and meta-analyses, focusing on cystic duct management techniques during LC. Particular attention was paid to comparing modern methods, such as vessel-sealing devices, with traditional ligation and clipping techniques.